Suppression of Breast Cancer Proliferation and Induction of Apoptosis via AKT and ERK1/2 Signal Transduction Pathways by Synthetic Polypeptide Derived from Viral Macrophage Inflammatory Protein - 杨清玲 陈昌杰 杨志峰 高艳军 唐洁 (华中科技大学学报：医学英德文版, 2011)
SDF-1α,a ligand for the chemokine receptor CXCR4,is well known for mediating the migration of breast cancer cells.In a previous study we demonstrated that a synthetic 21-mer peptide antagonist of CXCR4（NT21MP） derived from the viral macrophage inflammatory protein Ⅱ could antagonize tumor growth in vivo by inhibiting cellular proliferation and inducing apoptosis in breast cancer cells.However,the role of SDF-1α in the signaling pathways underlying the proliferation of human breast cancer cells and associated signaling pathways and inhibiting signal pathways of NT21MP remained unclear.The present study investigated the mechanism of NT21MP on anti-tumor in breast cancer in vitro.The effect of NT21MP on the viability of cells was determined by the MTT assay.Annexin V-FITC and PI staining was performed to detect early stage apoptosisin SKBR3 cells treated with SDF-1α and AMD3100 or NT21MP.Western blotting techniques were used to assay the composition of phosphoproteomics and total proteins present in the SKBR3 breast cancer cells.RT-PCR and Western blotting technique were used to detect the effect of NT21MP and AMD3100 on Bcl-2 and Bax expression.The results indicated that SDF-1α prevented apoptosis and promoted the proliferation of SKBR3 human breast cancer cells.As compared with untreated SKBR3 cells,Treatment with SDF-1α significantly increased cell viability,and NT21MP abolished the protective effects of SDF-1α dose-dependently（P0.05）.There was a significant decrease in the percentage of apoptotic cells after SDF-1α treatment as compared with control group（2.7%±0.2% vs.5.7%±0.4%,P0.05）.But pretreatment of SKBR3 cells with NT21MP significantly attenuated the antiapoptotic effects of SDF-1α as compared with SKBR3 cells without NT21MP pretreatment.The proliferative and anti-apoptotic effects of SDF-1α in SKBR3 cells were associated with an increase in AKT and ERK1/2 phosphorylation as well as a decrease in Bax expression and an increase in Bcl-2 expression.These changes in intracellular processes were blocked by NT21MP in a dose-dependent manner（P0.05）.In conclusion,NT21MP efficiently inhibits SDF-1α-induced proliferation and antiapoptosis in SKBR3 cells by reducing the levels of phosphorylated AKT and ERK1/2,as well as decreasing the ratio of expression of Bcl-2 relative to Bax.